MITIGASI BENCANA BERBASIS KEARIFAN LOKAL DI DESA TIENG, KABUPATEN WONOSOBO - Puspitasari, Anisa Eka; Bima, Dion Prabu Septa; Dewi, Titis Puspita (UI Scholars Hub, 2018)
Disaster is a common thing experienced by people in Indonesia and become its own problem. People who are accustomed to disaster have local knowledge in disaster mitigation. Local knowledge or local wisdom is the result of the adaptation and experience of events that have occurred in the area. This research takes place in Tieng Village, Dieng, Kejajar District, Wonosobo Regency. Tieng Village is an area prone to landslides and has been hit by flash flood on 18 December 2011. The flood disaster caused loss of life and loss of property that is not small. The research method used is descriptive qualitative with structural approach related to collective awareness of society. The purpose of this study is to analyze the mitigation efforts undertaken by local wisdom-based communities in Tieng Village. The result of this study is that people have a common awareness to perform the mitigation that is demonstrated by the habit of going out and going to safer places by bringing securities when there is heavy rain with high intensity more than two hours, once a month working to clean river and plant trees , often held socialization about floods and landslides especially when the rainy season, and people have an understanding that they must be wise to nature